12-Acetyl-6-hydroxy-3,3,9,9-tetramethylfuro[3,4-b]pyrano[3,2-h]-xanthene-7,11(3H,9H)-dione - Cheng, Gwendoline Lian Ee; Siow, Hwa Teo; Huey, Chong Kwong; Mohamed Tahir, Mohamed Ibrahim; Silong, Sidik (International Union of Crystallography, 2010)
The title compound, Artonol B, C24H20O7, isolated from the stem bark of Artocarpus kemando, consists of four six-membered rings and one five-membered ring. The tricyclic xanthone ring system is almost planar [maximum deviation 0.115 (5) Å], whereas the pyranoid ring is in a distorted boat conformation·The furan ring is almost coplanar with the fused aromatic ring, making a dihedral angle of 3.76 (9)°. The phenol ring serves as a intramolecular hydrogen-bond donor to the adjacent carbonyl group and also acts as an intermolecular hydrogen-bond acceptor for the methyl groups of adjacent molecules, forming a three-dimensional network in the crystal.